1972
DOI: 10.1136/hrt.34.5.472
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular conduction in acute rheumatic fever.

Abstract: A new study ofnormal PR intervals was undertakenfor the purposes of analysing atrioventricular conduction. Abnormalities of conduction were identified in 84 per cent of So8 patients with acute rheumatic fever. The PR index was used as a simple, reliable method of showing these changes. Such conduction disturbances occur more commonly than carditis, arthritis, subcutaneous nodules, chorea, or erythema marginatum, the five major features of the disease. Streptococcal infection and acute glomerulonephritis were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
13

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 14 publications
4
63
0
13
Order By: Relevance
“…[1][2][3] In 508 patients seen with ARF in Toronto from 1948-1971, 3 had ECG evidence of complete heart block. 4 The natural history tending to spontaneous resolution in this case is similar to other reports in the literature.…”
Section: Complete Heart Block Complicating Acute Rheumatic Feversupporting
confidence: 87%
“…[1][2][3] In 508 patients seen with ARF in Toronto from 1948-1971, 3 had ECG evidence of complete heart block. 4 The natural history tending to spontaneous resolution in this case is similar to other reports in the literature.…”
Section: Complete Heart Block Complicating Acute Rheumatic Feversupporting
confidence: 87%
“…The interpolated mean PR intervals at HR of 80, 90 and 100 beats min-1 were 149, 145 and 143 ms respectively for exercise and 140, 134 and 128 ms respectively for isoprenaline infusion and the differences between these paired data for individual subjects were statistically significant. Das et al (1975) and Atterhog & Loogna (1977 Although Cohn & Swift (1924) had recognised the prolongation of PR in children with acute rheumatic fever, it remained for Clarke & Keith (1972) to attempt a systematic evaluation of the possible confounding factor of heart rate. Clarke & Keith (1972) established upper limits for PR interval from resting cardiograms in 672 healthy children and determined that it was appropriate to define upper limits according to age.…”
Section: Resultsmentioning
confidence: 99%
“…Das et al (1975) and Atterhog & Loogna (1977 Although Cohn & Swift (1924) had recognised the prolongation of PR in children with acute rheumatic fever, it remained for Clarke & Keith (1972) to attempt a systematic evaluation of the possible confounding factor of heart rate. Clarke & Keith (1972) established upper limits for PR interval from resting cardiograms in 672 healthy children and determined that it was appropriate to define upper limits according to age. Furthermore, they concluded that there should be adjustment of observed PR interval according to the formula of Mirowski et al (1964) whose PR index is calculated by dividing measured PR by maximum normal PR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient required a temporary pacemaker and two patients were treated with corticosteroids. Other cases found prolonged PR intervals in 84% of 508 children with ARF, among these cases, 3 children had complete AV block, an done patient required artificial pacing [8]. Our patients advanced AV block reverted to first degree block with corticosteroid therapy after 3 days hospitalization and not to required pacemaker.…”
Section: Discussionmentioning
confidence: 51%